PENERAPAN APLIKASI AKSI UNTUK MENINGKATKAN LITERASI BACA SISWA KELAS 4 SD N 1 MURUH - Fadya Juliana Putri; Hardika Dwi Hermawan (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
The Covid-19 pandemic has made the already massive learning difficulties in developing countries more severe than ever. The percentage of children who cannot read simple texts with comprehension by the time they are 10 years old is one of the clearest indications of learning problems. For this reason, the Ministry of Education and Culture created an application that can support the improvement of student literacy called AKSI. This study aims to determine the application of AKSI application to improve the reading literacy of 4th grade students of SD N 1 Muruh. The method used is qualitative. Data collection techniques were conducted through observation, interviews, and documentation. The data analysis process includes data reduction, data presentation and conclusion drawing. AKSI application with all its features can be an alternative learning resource that can increase elementary students' reading literacy interest and in accordance with technological developments and can support students' reading habits at school and at home.